How Aspirin Entered Our Medicine Cabinet - Rooney, Steven M.; Campbell, J.N (History of Chemistry, 2017)
This brief traces the story of one of our most common medicines - aspirin. On a journey involving science, diverse characters, shady business deals, innovative advertising and good old-fashioned luck, Rooney and Campbell describe how aspirin was developed and marketed on a global scale. Starting at the beginning of the twentieth century, the authors explain the use of aspirin during the First World War, the development of competition drugs such as ibuprofen during the interwar years, and the application of aspirin to heart disease in the 1950s and 1960s. On a broader level, Rooney and Campbell show that the development of America's modern pharmaceuticals was a complex weaving of chemistry and mass culture. They argue that aspirin's story provides a way to understand the application of complex chemical formulas in medical results. This brief is of interest to historians of chemistry and medicine as well as the general educated reader.